Neonatal Sex Assignment in Disorders of Sex Development: A Philosophical Introspection - V Raveenthiran (EL-Med-Pub, 2017)
Management of ambiguous genitalia is highly controversial. This condition was known previously as intersex and presently as disorders of sex development (DSD). There is no consensus regarding the choice, timing and method of sex assignment in neonates with DSD. Consensus conferences could not unify the views of various stakeholders and third parties. This article philosophically examines the nature and origin of such controversies. Misconception, bias and conflicting priorities are identified as the three cardinal sources of controversies. Conceptual duality of sexes, confused notion of sex and gender, bias towards penetrative intercourse, conflict between utopian ideals and reality, unwillingness to compromise are identified as perpetuators of controversies. Suggestions are made regarding sex assignment in various types of DSD based on the understanding of published literature and the author's personal experience.